How to time the time ‐ A preface to the special issue Circadian Rhythms in the Brain. Issue 1 (16th March 2021) - Stehle, Jörg H.; Zemmar, Ajmal; Hausmann, Laura
Abstract: In this Preface to the Journal of Neurochemistry special issue "Circadian Rhythms in the Brain", we summarize recent insights into connections between circadian rhythms and societal concerns related to aging and food intake, with consequences for healthy or aberrant metabolic homeostasis. The articles in this special issue were written by leading authors who presented their research at the 2019 Congress of the European Biological Rhythm Society, and are thus reflective of a broad variety of state‐of‐the‐art research on all levels of chronobiology, from circadian rhythm generators in various tissues (including astrocytes) and the molecular mechanisms they base on, such as GABAergic regulation or ubiquitination, to the systems and behavioral level effects of chrono‐nutrition and aging. Cover Image for this issue:  https://doi.org/10.1111/jnc.15058 . Abstract : In this Preface to the Journal of Neurochemistry special issue "Circadian Rhythms in the Brain", we summarize recent insights into connections between circadian rhythms and societal concerns related to aging and food intake, with consequences for healthy or aberrant metabolic homeostasis. The articles were written by lead authors who presented their research at the 2019 Congress of the European Biological Rhythm Society, and are thus reflective of a broad variety of state‐of‐the‐art research on all levels of chronobiology, from clock generators in various tissues (including astrocytes) and the molecular mechanisms they base on, such as GABAergic regulation or ubiquitination, to the systems and behavioral level effects of chrono‐nutrition and aging. Cover Image for this issue:  https://doi.org/10.1111/jnc.15058 .